Recursos didácticos y su incidencia en el desarrollo de la creatividad de los niños del subnivel 2 de la Unidad Educativa Víctor Emilio Estrada - Herrera Vera, Dellaneira Yomira (2023)
Didactic resources are very important tools in education because they facilitate the learning of infants, especially at the initial level since they encourage the child's creativity and imagination and enhance motor skills and abilities. For this reason, it is crucial that educators use the appropriate resources that ensure an optimal learning experience. The objective of this study is to determine the impact of teaching resources on the creative development of children in sublevel II, of the Víctor Emilio Estrada Educational Unit, Vinces Canton, Los Ríos Province. For which it was necessary to implement a non-experimental research design and mixed approach. The types of research were descriptive, documentary and field. The investigative techniques contemplated in the case study are: a survey and an observation; while the instruments were a questionnaire of questions and an observation sheet. The population was made up of 23 students and 23 parents from sublevel II of the aforementioned institution. The results of the research allowed us to conclude that the teaching resources implemented by the teacher for the development of creativity of the children of sublevel II, of the Víctor Emilio Estrada Educational Unit, are scarce and lack variety and innovation, making the teaching process learning is monotonous and less interesting for children, resulting in a decrease in their motivation to actively participate in educational activities and develop their creativity.